Mother Nature’s Revolution and the COVID-19 Pandemic: A Scooping Review of COVID-19 and the Environment - Uzobo, Endurance; Boroh, Stanley E. (European Scientific Journal, ESJ, 2021)
Many studies have solely focused on the negative impact of the coronavirus while ignoring the fact that the coronavirus was also a blessing in disguise to certain institutions. This study focuses on an exploration of some of the environmental-related benefits accruing from the outbreak of the coronavirus, which eventually led many countries of the world to declare a national lockdown. The study utilised secondary sources from 21 articles gleaned from hand-searched literature from various web pages and online news, accessed through google web page (google.com) between March to September 2020. Key search words used in the search were COVID-19 and the environment, benefits of COVID-19 to the environment, the environmental impact of COVID-19, and the environmental behaviour during COVID-19. The study reported that some positive benefits of COVID-19 concerning the environment from China, the United States of America, Europe, and Africa. Findings from the review indicated that almost all the continents in the world have experienced improve environmental quality as a result of the outbreak of the coronavirus. The study further added that one of the most important dividends arising from the outbreak is the positive change in behaviour in people towards the environment. It was, therefore, recommended that there is a need for nations of the world to leverage the window of opportunity provided by the coronavirus to encourage green economic behaviour to save the environment.